FAKTOR RISIKO KEJADIAN ISPA NON PNEUMONIA PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA KOTA PEKANBARU - Nahabila, T. Sy Rafni; Lapau, Buchari; -, Herniwanti - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
ISPA Non pneumonia is a symptom of cough that does not show symptoms of an increase in the frequency of breath and does not also show the pull of the lower chest wall towards the inside. The purpose of this study was to find out the factors associated with the incidence of ISPA non-pneumonia in children under five in the working area of Harapan Raya Community Health Center in Pekanbaru City in 2018. This research was quantitative observational analytic with the type of Analytical Cross-sectional Study design. This study was conducted from June to July 2018. Data analysis was carried out in stages which included univariate analysis, bivariate analysis and multivariate analysis. The sampling procedure was carried out by systematic random sampling with a sample of 212 toddlers. The results of the study showed that toddlers who suffered from ISPA non-pneumonia in the sample were 60.44%. And in the population is 60.44% Â± 5% = 55.44% -65.44%. Variables related to cause and effect are mosquito coils, the presence of smokers and room temperature. Variables are inversely correlated, namely natural lighting variables. Counfounding variable is the variable of ventilation against natural lighting variables. Unrelated variables are humidity, ventilation, house walls, density of house occupancy, cooking fuel usage, age, and sex.